2010
DOI: 10.1002/ijc.25714
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for distinguishing optimal cancer subtypes

Abstract: Much attention is directed currently to identifying subtypes of cancers that are genetically and clinically distinct. The expectation is that subtyping on the basis of somatic genomic characteristics will supplant traditional pathological subtypes with respect to relevance for targeted therapies and clinical course. Less attention has been paid to the goal of validating subtypes on the basis of the distinctiveness of their etiologies. In this article it is shown that studies of individuals with double primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…More recently, the concept of Molecular Pathological Epidemiology proposed by Ogino et al 90,91 may provide a useful route in dissecting the interactive effects between tumour biomarkers, such as COX-2, and aspirin exposure. 90,91 This concept, similar to proposals by Begg et al 92 and Curtin et al, 66 combines traditional epidemio logical assessment of cancer risk factors, with traditional molecular pathology-with the aim of evaluating the impact of environmental exposures (such as, aspirin) on the molecular signatures of tumours. 92,66 This inter sectional approach may be useful in enabling researchers to tease apart the interactive effects of prior aspirin exposure, tumour location, MSI and CIMP status, COX-2 expression, and response to treatment.…”
Section: Biomarkersmentioning
confidence: 93%
See 1 more Smart Citation
“…More recently, the concept of Molecular Pathological Epidemiology proposed by Ogino et al 90,91 may provide a useful route in dissecting the interactive effects between tumour biomarkers, such as COX-2, and aspirin exposure. 90,91 This concept, similar to proposals by Begg et al 92 and Curtin et al, 66 combines traditional epidemio logical assessment of cancer risk factors, with traditional molecular pathology-with the aim of evaluating the impact of environmental exposures (such as, aspirin) on the molecular signatures of tumours. 92,66 This inter sectional approach may be useful in enabling researchers to tease apart the interactive effects of prior aspirin exposure, tumour location, MSI and CIMP status, COX-2 expression, and response to treatment.…”
Section: Biomarkersmentioning
confidence: 93%
“…90,91 This concept, similar to proposals by Begg et al 92 and Curtin et al, 66 combines traditional epidemio logical assessment of cancer risk factors, with traditional molecular pathology-with the aim of evaluating the impact of environmental exposures (such as, aspirin) on the molecular signatures of tumours. 92,66 This inter sectional approach may be useful in enabling researchers to tease apart the interactive effects of prior aspirin exposure, tumour location, MSI and CIMP status, COX-2 expression, and response to treatment. Furthermore, Molecular Pathology Epidemiology has the potential to provide interesting clues concerning the relationship between tumour molecular features, and the adaptive immune response.…”
Section: Biomarkersmentioning
confidence: 93%
“…Despite this anatomic independence, a number of studies have shown that synchronous and metachronous bilateral breast cancers tend to demonstrate concordance in expression status for the hormone receptors ESR1 (estrogen receptor-alpha), and PGR (progesterone receptor). 71 These data imply that, in bilateral breast cancer, independent primary tumors tend to evolve through similar carcinogenic pathways, compared to cancers arising in two different individuals.…”
Section: Synchronous Primary Tumors and Field Effect: Insights And Inmentioning
confidence: 97%
“…13–17 Alternatively, it can be considered that synchronous primary tumors arise through the interplay between common etiologic contributors, such as genetic predisposition, microbial and environmental exposures, and lifestyle factors, which facilitate progression through certain common carcinogenic pathways. 65, 67, 71 Importantly, the latter model does not imply that the molecular features shared by synchronous tumors need to be present in the background ‘normal-appearing’ tissue.…”
Section: Synchronous Primary Tumors and Field Effect: Insights And Inmentioning
confidence: 99%
“…This facilitates the exploration of countless sub-typing options to identify the set or sets that possess the greatest evidence of heterogeneity. [64] He also explained the unique insights that can be obtained by investigating and correlating the mutational profiles of double primary malignancies,[123] and illustrated the concepts using studies of breast cancer, melanoma and kidney cancer.…”
Section: Statistical Opportunities and Challenges In Mpementioning
confidence: 99%